Dialektika Sanksi Pidana Mati Dalam Bangunan Hukum Pidana Yang Berkeadilan - Palguna, I Dewa Gede; Sugi Hartono, I Made (Kertha Patrika; Vol 46 No 1 (2024), 2024)
In this study aims to unravel the synthesis of dialectics that hold and negate the formulation of death penalty sanctions in Indonesian criminal law. Using juridical-normative method, secondary data consisting of primary, secondary and tertiary legal materials are collected through document and literature study techniques and analyzed descriptively-qualitatively. The scientific mind of criminal law has undergone development from classical to modern to neo-classical (daad strafrecht to dader strafrecht to the last daad-dader strafrecht). In relation to death penalty sanction, through the Constitutional Court Decision Number 2-3/PUU-V/2007, the state has firmly determined its constitutionality although there is an interpretation that is not fully in line with one Supreme Court cassation decision Number 39 PK/Pid.Sus/2011 which is based on international developments in various countries that the death penalty sanction has been abolished. This study produces findings that the Indonesian criminal law policy related to the formulation of the death penalty sanction is a synthesis between the thesis that holds and the antithesis that negates according to the formulation in Law Number 1 of 2023 concerning the Criminal Code (KUHP) that the death penalty sanction is a special type of criminal sanction carried out through a probationary period and can then be changed to a type of life imprisonment or for a maximum period of 20 years if it meets certain qualifications. The pursuit of fair and usefulness criminal law is a dialectical process with a positioning on the balance between individual protection and collective interests.